Can neutrophil-to-lymphocyte ratio and proatherogenic risk factors improve the accuracy of pneumonia severity index in the prediction of community acquired pneumonia outcome in healthy individuals? - Aida Mujaković; Belma Paralija; Orhan Lepara; Almir Fajkić; Avdo Kurtović; Besim Prnjavorac; Edin Begić; Nejra Gondžetović-Ćorić (Medicinski glasnik, 2022)
Aim: To investigate influence of neutrophil-to-lymphocyte ratio (NLR) and proatherogenic risk factors to improve the accuracy of pneumonia severity index (PSI) in the prediction of community acquired pneumonia (CAP) outcome in healthy individuals. Methods: A retrospective observational cross-sectional study conducted at the Clinic for Pulmonary Diseases and Tuberculosis “Podhrastovi”, University Clinical Centre Sarajevo, included 83 patients with the diagnosis of CAP during the period March 2019-March 2021. Once diagnosed with CAP, PSI score was calculated and according to its value the need for hospital treatment was identified. Patients were divided in two groups: low risk of CAP (PSI <90), and high risk of CAP (PSI> 90). Results: The overall average hospital stay was 22.76±10.154 days. In the patients diagnosed with CAP, a positive correlation was established between the following parameters PSI score and age (r=0.670; p<0.01), C-reactive protein-CRP (rho=0.287; p<0.01), leukocytes (rho=0.406; p<0.01), NLR (rho=0.313; p<0.01) and platelet to lymphocyte ratio (PLR) (0.296; p<0.05). CRP, leukocytes, NLR and PLR were statistically significantly higher in patients with high risk of CAP compared to patients with low risk of CAP. Diastolic blood pressure, lymphocytes, eosinophils were significantly lower in patients with high risk of CAP (p<0.05;) compared to patients with low risk of CAP (p<0.01). The optimal cut-off value of NLR for CAP patients was 3.089 with an estimated area under curve (AUC) of 0.664. Conclusion: Proatherogenic parameters such as age, systolic blood pressure and leukocytes in combination with neutrophil-lymphocyte count ratio could improve accuracy of the pneumonia severity index in community acquired pneumonia outcome.
Keywords: atherosclerosis; inflammation; lung